Comparative analysis of the preference of producers and processors for domestic rice production contracts in Benin - Codjo, Simon Ogoudélé; ACCLASSATO, HOUENSOU DÉNIS; Fiamohe, EMILE DIDIER; Kpenavoun Chogou, Sylvain; BIAOU, GAUTHIER (My University, 2019)
This study aims to analyze the factors that influence the preference of producers and processors for paddy production contracts in Benin. Unlike previous research, this study estimates a global model using pooled data of producers and processors. In addition, it compares producers’ willingness to accept contracts’ attributes to processors willingness to pay for the same attributes. Data were collected in Benin from 300 producers and 140 processors of rice selected randomly. An estimation of the conditional logit model indicates that producers prefer contracts specifying cash payment, prefinancing, and quality agreement. Processors, on the other hand, prefer contracts specifying technical assistance for both harvest and all the production activities, and quality agreements. The latent class logit model shows that there is heterogeneity among the preferences of both producers and processors across the classes. However, producers prefer cash payment and processors assistance for harvesting across all the classes. This suggests that cash payment and assistance for nharvesting are pivotal for contract selection by producers and processors, respectively. Producers are willing to accept a lower price for their paddy (reduction of 25.86 and 6.64 FCFA/kg) in exchange for specifying a cash payment mechanism and prefinancing in the contract. Processors are willing to pay an additional amount of 5.58 CFA/kg of paddy to secure good quality rice.
Keywords: Paddy; rice; Benin; payment mechanism; prefinancing in the contract